Microphysical Parameterization Scheme with Satellite Data Verification and Observation Data for Analysis of Heavy Rain in Yogyakarta City - Prima, Rajab; Athallah, Muhammad Syauqi Bima; Ramadhani , Gema Reksa (Tinta Emas Publisher, 2024)
The numerical weather prediction model Weather Research and Forecasting - Advanced Research WRF (WRF-ARW) was used to simulate the atmospheric conditions during heavy rainfall in the Yogyakarta area on February 3, 2022. Several parameterization schemes were compared with observational data to obtain the best choice of microphysical parameterization scheme in describing the atmospheric conditions at the time of the event. The microphysical parameterization schemes used are: Kessler, Purdue Lin, and WRF Single-Moment. Class (WSM3). The verification results show that the Kessler microphysical parameterization scheme has the best performance in representing heavy rain events with a fairly high low cloud fraction data accuracy value ranging from 0.3 - 0.4 and the highest rainfall modeling value is 8.3 mm. It can be concluded that the Kessler scheme is sufficient to model the occurrence of heavy rain in the city of Yogyakarta.